Systemic Requirements for Monetary Stability in Eastern Europe and the Former Soviet Union - Rostowski, Jacek (IMF Working Papers; Working Paper ;, 1994)
The primary function of banks during economic transformation is seen to be provision of an efficient payments mechanism. The lack of banking skills, particularly in credit allocation, is seen as the major problem in stable monetary systems. This is a problem which can be expected to last many years. The solution is to limit banks to very safe assets (initially central bank liabilities). Combining such safe banks with a monetary rule would provide stable monetary systems during transition.